Limited association between markers of stress during pregnancy and fetal growth in 'Born into Life', a new prospective birth cohort. (22nd February 2018) - Smew, Awad I.; Hedman, Anna M.; Chiesa, Flaminia; Ullemar, Vilhelmina; Andolf, Ellika; Pershagen, Göran; Almqvist, Catarina
Abstract: Aims: We aimed to investigate the associations between perceived maternal stress or salivary cortisol levels during pregnancy and birthweight. Methods: In 2010–2012, we recruited 92 women living in Stockholm, Sweden, and followed them from before conception and through pregnancy and childbirth. Their Perceived Stress Scale (PSS) scores and salivary cortisol levels were collected at 26–28 gestational weeks. Birthweight was collected from medical records. Linear regression analyses and Pearson correlations were performed between the PSS scores or cortisol levels and birthweight, respectively, adjusted for gestational age. Results: No significant associations were found between PSS scores or cortisol levels and birthweight. There was a trend towards higher salivary cortisol levels among infants with lower birthweights, and this effect was attenuated after adjusting for gestational age. Morning cortisol levels (r = −0.31, p = 0.01), the decline in cortisol levels (r = −0.26, p = 0.03) and evening cortisol levels (r = −0.21, p = 0.09) were negatively correlated with PSS scores. Conclusion: Maternal stress during pregnancy was not associated with birthweight. The inverse correlation between PSS scores and cortisol levels may indicate other mechanisms for maternal stress on child outcomes than the previous explanation of hypothalamic‐pituitary‐adrenal axis activity.